Wide-Field-of-View Modulating Retro-Reflector System Based on a Telecentric Lens for High-Speed Free-Space Optical Communication - Jiahan Tian; Tingbiao Guo; Nan He; Ji Du; Qiangsheng Huang; Xiaojian Hong; Chao Fei; Yuan Wang; Tianyi Zhang; Junping Zhang; Sailing He (IEEE Photonics Journal, 2023)
Modulating retro-reflector (MRR) free-space optical (FSO) communication technology presents a bright future for realizing the small size, weight, and power (SWaP) design of one end of the optical link, facilitating the further application of the FSO communication to the small platforms. However, the limited field-of-view (FOV) of MRR impedes its wide employment. In this article, a novel wide-FOV MRR using an image space telecentric lens is proposed and a bidirectional FSO communication system is experimentally demonstrated using this MRR with a single light source. The performance of the telecentric lens between the transceiver and terminal is assessed by simulation and also validated by experimental results, with a coupling loss less than 9.1 dB within a FOV of 110°. Both 10-Gbit/s on-off keying (OOK) downstream and upstream signals for free space communication at different incident angles are successfully realized using this designed wide-FOV MRR. The experimental results validate the proposed MRR has a FOV of up to 110° where the measured bit error rate (BER) is lower than 3.8 × 10−3 for both downstream and upstream signals. To the best of our knowledge, this is the largest FOV ever reported for MRRs in high-speed bidirectional FSO communication systems.